Peningkatan kualitas SDM Batik Riau melalui pelatihan membatik (ARSY : Jurnal Aplikasi Riset kepada Masyarakat, 2024)
This community service program aims to enhance the quality of human resources (HR) among Riau batik artisans through comprehensive batik training. Riau batik, as a cultural heritage with high aesthetic and historical value, faces challenges in maintaining its sustainability and competitiveness amidst evolving market demands and trends. The primary challenge is the lack of skills and knowledge among artisans in batik techniques, design innovation, and the use of eco-friendly materials. The training, led by a batik expert, provides artisans with new skills in design, coloring, and batik techniques, along with effective marketing strategies to boost Riau batik's appeal in both national and international markets. The results of the program show significant improvements in the quality of batik products, as well as innovations in motifs and designs that better align with market preferences. Consequently, this training is expected to contribute to the preservation and development of Riau batik and improve the livelihoods of local batik artisans.
Keywords: Batik Riau; pelatihan membatik; kualitas SDM; inovasi desain; pemasaran